Influência da adição de tensoativos em redes de sílica para adsorção de corantes - Buzato, Gabriel Vinicius (Universidade Federal de São Carlos, 2022)
Synthetic dyes, normally used industrially, when discarded incorrectly can cause damage to the environment and human life, inhibiting the passage of light in water bodies and hindering the photosynthesis of plants and algae in the aquatic environment. There are several studies with materials capable of adsorbing these harmful compounds, such as carbon nanotubes, but few with silica xerogels modified with surfactants. The adsorption capacity of silica xerogels against methyl orange and crystal violet dyes and the effect of cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS) surfactants incorporated into the xerogels in the adsorption process were evaluated here. To identify the bonds present in the materials, absorption spectroscopy was used in the infrared region with Fourier transform. For analysis of the pore diameter distribution, the Barrett-Joyner-Halenda (BJH) method was used through Nitrogen adsorption and desorption isotherms. Ultraviolet-visible spectroscopy was used to monitor dye adsorption. The adsorptions of the dyes indicated a better fit to the pseudo-second order kinetic model with a determination coefficient greater than 0.90. The experimental data fit better to the nonlinear model of Langmuir with a qmax value of 25.8 mg g-1 for the adsorption of crystal violet by the SDS-modified silica xerogel and 25.54 mg g-1 for the adsorption of methyl orange by the CTAB-modified silica xerogel. It was important to evaluate the adsorption efficiency of silica xerogels, as these are low-cost materials and could be used to remove toxic compounds from industrial effluents.
Influence of the addition of surfactants in silica lattice for dye adsorption
Keywords: Adsorção; Xerogéis; Tensoativos; Corantes; Adsorption; Xerogels; Surfactants; Dyes; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA